Victimization Among Incarcerated Military Veterans: A Target Congruence Approach - Logan, Matthew W. (Criminal justice policy review, 2023)
Studies explicitly examining the antecedents of prison victimization are rare relative to other institutional outcomes (e.g., misconduct) and are virtually nonexistent for incarcerated military veterans. In the current study, we employed Firth regression models to predict victimization among a subsample of military veterans housed by the Minnesota Department of Corrections (MnDOC) using a target congruence approach. Inconsistent with prior theory and research, we observed no differences among veterans on the basis of race and physical or mental health disorders. We did, however, observe a relationship between an individual’s risk of recidivism as measured by the MnSTARR 2.0 and victimization whereby higher scores corresponded with greater odds of victimization. Implications for theory and correctional policy are discussed and directions for future research are given.